Rb-Sr and Sm-Nd mineral isochron ages of a pegmatitic gneiss from Oku-iwa Rock, Lutzow-Holm Complex, East Antarctica - Kawano, Yoshinobu; Nishi, Naoko; Kagami, Hiroo (National Institute of Polar Research, 2006)
P(論文) Oku-iwa Rock is located in the transitional zone between granulite- and amphibolite-facies metamorphic zones in the Lutzow-Holm Complex (LHC), East Antarctica. Hornblende biotite (HB) gneiss widely outcrops in the northern part of this area. Sm-Nd and Rb-Sr mineral isochron ages obtained from pegmatitic HB gneiss are 578±36Ma and 431±14Ma with initial isotopic ratios of 0.511892±0.000040 and 0.70718±0.00038, respectively. The former mineral isochron age is consistent with the Rb-Sr whole rock isochron age of the HB gneiss (583Ma). The latter age is close to the previously published Rb-Sr mineral isochron age of granitic rocks (418Ma) in Oku-iwa Rock, implying that these ages represent the time when the rocks cooled down to the closure temperature of biotite. The granodioritic precursor formed at 674Ma was gradually cooled down and its temperature reached 700°C at 583Ma based on a previous report. Temperature of the HB gneiss rose at 578Ma by injection of source material for the pegmatitic HB gneiss and rose again at 529Ma (SHRIMP U-Pb zircon age) by regional metamorphism. At 485Ma, the temperature of the gneisses rose for the third time by intrusion of granitic rocks. After the intrusion, the constituent rocks of Oku-iwa Rock gradually cooled by uplifting and the temperature reached 310°C at 431Ma. departmental bulletin paper